The Meaning of Worship for Religious People in The Covid-19 Pandemic: a Phenomenological Research - Yopi Kusmiati; Kalsum Minangsih; Tantya Legistiana; Edi Santoso; YP Wahyu Gunawan; Yanti Hermawati (FAKULTAS DAKWAH UIN SALATIGA, 2024)
This research examines the meaning of worship in five religions (Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism) in Indonesia referring to phenomenological research. The research method used in this research is a qualitative method with a phenomenological approach. The data collection techniques used in this research were observation, in-depth interviews, and documentation. This study's informants used as research subjects were religious figures and followers of Islam, Catholic Christians, Protestant Christians, Buddhists, Hindus, and Confucians. This research found several ideas for worship during the COVID-19 pandemic. First, those who think there is no difference in the implementation of worship before and during the pandemic. Second, those who worship at home during the pandemic follow government regulations. Based on the opinions of informants who have explained many things regarding the implementation of worship during the pandemic, it can be concluded that several meanings of worship are worshiping with a sincere heart, purity of orientation, presenting God in the heart, praising God, listening to God's word, and being transcendental. Twenty-three informants may continue to pray at places of worship during the pandemic, and fifteen informants pray at home, according to policies issued by the government.